How to assess severity in males with eating disorders? The DSM-5 severity index versus severity based on drive for thinness. (13th April 2021) - Dang, A.; Krug, I.; Granero, R.; Agüera, Z.; Sánchez, I.; Riesco, N.; Jimenez-Murcia, S.; Fernandez-Aranda, F.
Abstract : Introduction: The Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) introduced severity indices for Eating Disorders (ED). Objectives: This study assessed in a male ED sample the DSM-5 severity indices for Anorexia Nervosa (AN), Bulimia Nervosa (BN) and Binge Eating Disorder (BED) and compared them to an alternative transdiagnostic drive for thinness (DT) severity category and a combined DSM-5/DT severity categorization Methods: 178 males with EDs were classified using: a.) a DT categorisation based on the EDI-2 DT subscale; b.) the DSM-5 severity categories for AN, BN and BED and c.) a combination of the DT and the DSM-5 severity categorisation. These severity classifications were then compared based on psychopathology and personality. Results: For the DSM-5 severity indices, the "mild" category was most prevalent for AN and BN, and the "moderate to extreme" group for BED. For the EDI-2 DT severity classification, the "mild" category was overrepresented in all subtypes. For the combined DSM-5/DT categorization, the "mild combined" severity group was the most prevalent for AN, while for BN and BED the "severe/extreme" combined group was most prevalent. Clinically significant findings were strongest for the DT categorization followed by the combined DSM-5/DT approach. Almost non-significant findings were revealed for the DSM-5 severity categories for all ED subtypes. These findings were most pronounced for AN and BN and almost non-existent for BED. Conclusions: Our findings provide support for DT as an alternative transdiagnostic severity category for EDs in males that may be more meaningful than the DSM-5 severity indices for AN and BN, but not BED. Disclosure: No significant relationships.